The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/btpr.2808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preheating on briquetting and subsequent hydrothermal pretreatment for enzymatic saccharification of wheat straw

Abstract: Briquetting of plant biomass with low bulk density is an advantage for handling, transport, and storage of the material, and heating of the biomass prior to the briquetting facilitates the densification process and improves the physical properties of the briquettes. This study investigates the effects of preheating prior to briquetting of wheat straw (WS) on subsequent hydrothermal pretreatment and enzymatic conversion to fermentable sugars. WS (11% moisture content) was densified to briquettes under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…12 Biomass densification is commonly applied to increase bulk density and facilitate biomass transportation. 13,14 Many studies have concluded that densification has different effects ( positive, neutral, and negative effects) on enzymatic saccharification of biomass. [15][16][17] As for positive effects, disruption of biomass structure caused by mechanical action (such as shearing, compressing, grinding, etc.…”
Section: Introductionmentioning
confidence: 99%
“…12 Biomass densification is commonly applied to increase bulk density and facilitate biomass transportation. 13,14 Many studies have concluded that densification has different effects ( positive, neutral, and negative effects) on enzymatic saccharification of biomass. [15][16][17] As for positive effects, disruption of biomass structure caused by mechanical action (such as shearing, compressing, grinding, etc.…”
Section: Introductionmentioning
confidence: 99%